Primerjalna analiza germanskih, romanskih in slovanskih ljudskih pravljic na primeru motiva živalskega ženina oz. živalske neveste - Blažič, Milena (Slavistična revija, 2008)
The study is a comparative analysis of the collection of German tales by Jakob and Wilhelm Grimm Children's and Household Tales (1812, 2006), Romance fairy tales (a new discovery by American scholar Jack Zipes), compiled by Laura Gonzenbach in the collection Beautiful angiola (1879, 2006), and a collection of Slovene Fairy Tales (2002(. The comparative analysis of the same motif is based on the structuralist theory of Russian ascholar Vladimir Propp (Morhpology of the folktale, 1928, 2006), folkloristic theory of motifs by the American folklorist Stith Thompson (Motif-index of Folk Literature, 1989), literary theory if the Swiss scholar Max Lüthi (The European Folktales: Form and Nature, 1947, 1986), psychoanalitic theory of Bruno Bettelheim (The Uses of Enchantment, 2001), sociologic theory of Jack Zipes (Why Fairy Tales Stick, 2006), feminist theory of Clarissa Pinkola Estés (Women Who Run with the Wolves, 2001), and post-structuralist theory of Maria Nikolajeva (Fairy Tale and Fantasy, 2003). The comparative analysis of general similarities and differences focuses on the study of the motif of the animal goom or animal bride in all three collections of fairy tales. The findings of the comparative analysis of this motif also present a comparative analysis of similarities and diifferenes between Germanic, Romance, and Slavic variant of the folktale. The findings of the comparative analysis are presented at the end of the study.
Keywords: ljudske pravljice; motivika; pravljice; primerjalna analiza; živali